Leptin Suppression of Insulin Secretion by the Activation of ATP-Sensitive K+ Channels in Pancreatic β-Cells - Timothy J. Kieffer; R. Scott Heller; Colin A. Leech; George G. Holz; Joel F. Habener (1997)
In the genetic mutant mouse models ob/ob or db/db, leptin deficiency or resistance, respectively, results in severe obesity and the development of a syndrome resembling NIDDM. One of the earliest manifestations in these mutant mice is hyperinsulinemia, suggesting that leptin may normally directly suppress the secretion of insulin. Here, we show that pancreatic islets express a long (signal-transducing) form of leptin-receptor mRNA and that β-cells bind a fluorescent derivative of leptin (Cy3-leptin). The expression of leptin receptors on insulin-secreting β-cells was also visualized utilizing antisera generated against an extracellular epitope of the receptor. A functional role for the β-cell leptin receptor is indicated by our observation that leptin (100 ng/ml) suppressed the secretion of insulin from islets isolated from ob/ob mice. Furthermore, leptin produced a marked lowering of ]Ca2+]i in ob/ob β-cells, which was accompanied by cellular hyperpolarization and increased membrane conductance. Cell-attached patch measurements of ob/ob β-Cells demonstrated that leptin activated ATP-sensitive potassium channels (KATP) by increasing the open channel probability, while exerting no effect on mean open time. These effects were reversed by the sulfonylurea tolbutamide, a specific inhibitor of KATP. Taken together, these observations indicate an important physiological role for leptin as an inhibitor of insulin secretion and lead us to propose that the failure of leptin to inhibit insulin secretion from the β-Cells of ob/ob and db/db mice may explain, in part, the development of hyperinsulinemia, insulin resistance, and the progression to NIDDM.